Biomarkers of Inflammation and Fibrosis in Kawasaki Disease Patients Years After Initial Presentation With Low Ejection Fraction. Issue 1 (7th January 2020) - Hoshino, Shinsuke; Shimizu, Chisato; Jain, Sonia; He, Feng; Tremoulet, Adriana H.; Burns, Jane C.
Abstract : Background: Coronary artery aneurysms and myocarditis are well‐recognized complications of Kawasaki disease (KD) but no systematic evaluation of the consequences of myocarditis has been performed in the subset presenting with low ejection fraction (EF). We postulated that more severe myocardial inflammation as evidenced by low EF during the acute phase could lead to late myocardial fibrosis. Methods and Results: We measured the carboxyterminal propeptide of procollagen type I (PIPC), soluble suppressor of tumorigenicity 2, galectin‐3 (Gal‐3), growth‐differentiation factor‐15, and calprotectin by ELISA in late convalescent blood samples from 16 KD patients who had an EF ≤55% on their initial echocardiogram. Results were compared with samples from sex‐ and age‐matched KD patients with initial EF >60%. In the univariate analysis, the median Gal‐3 and PIPC levels in the low EF group were significantly higher than those in the normal EF group (Gal‐3: low EF 6.216 versus normal EF 4.976 mg/dL P =0.038, PIPC: low EF 427.4 versus normal EF 265.2 mg/dL, P =0.01). In a multivariable analysis, there were significant differences for Gal‐3 and PIPC levels between the low and normal EF groups, adjusting for age, sex, and worst z score. Conclusions: Convalescent KD patients with a history of low EF during the acute illness had significantly elevated levels of Gal‐3 and PIPC when compared with matched‐control KD patients with normal EF. These findings raise concern for myocardial fibrosis as a potential late sequela of the more severe myocarditis experienced by a subset of KD patients during the acute phase.